2015
DOI: 10.1160/th14-03-0217
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Ibα clustering induces macrophage-mediated platelet clearance in the liver

Abstract: Many immune thrombocytopenia (ITP) patients, particularly patients with anti-glycoprotein (GP) Ib-IX autoantibodies, do not respond to the conventional treatments such as splenectomy. However, the underlying mechanism remains unclear. Here we found that anti-GPIbα N-terminus antibody AN51, but not other anti-GPIbα antibodies (AK2, HIP1, VM16d, or WM23), induced GPIbα clustering that led to integrin αIIbβ3-dependent platelet aggregation. After intravenous injection, AN51 dose-dependently induced thrombocytopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Recent reports have suggested that exposure of β-galactose and/or N-acetyl-glucosamine on the to-be-cleared platelet, as a result of deglycosylation, can mediate platelet clearance 3235 . Particularly, the change of glycans in the extracellular domain of GPIbα has been implicated 32, 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that exposure of β-galactose and/or N-acetyl-glucosamine on the to-be-cleared platelet, as a result of deglycosylation, can mediate platelet clearance 3235 . Particularly, the change of glycans in the extracellular domain of GPIbα has been implicated 32, 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that many antibodies targeting GPIbβ and GPIX subunits in the GPIb-IX complex do not cause platelet clearance [74-76]. It has also been recently reported that not all anti-GPIbα antibodies induce platelet clearance [77, 78]. It is likely that platelets secrete active Neu1 and Neu3 upon antibody binding and/or platelet activation [30].…”
Section: Immune Platelet Clearancementioning
confidence: 99%
“…Prior to this study, it was known that antibodies to the GPIba subunit mimic the natural GPIba ligand, von Willebrand factor (VWF), to initiate GPIba-mediated signal transduction, platelet activation, and clearance in the liver. 3 This activation pathway requires a dimeric form of the antibody, implying that GPIb-IX signals when clustered. 3 However, it was soon learned that dimerization of GPIba is not enough to activate platelets.…”
mentioning
confidence: 99%
“…3 This activation pathway requires a dimeric form of the antibody, implying that GPIb-IX signals when clustered. 3 However, it was soon learned that dimerization of GPIba is not enough to activate platelets. 4 Instead, GPIb-IX is a mechanoreceptor, meaning it signals when pulled.…”
mentioning
confidence: 99%
See 1 more Smart Citation